Experimental and numerical studies of screwed connections with hot-rolled steel plate and cold-formed steel sheet. (May 2023) - Liu, Shen; Feng, Ruoqiang; Zhong, Yuting
Abstract: This paper presents a test and numerical program on screwed connections of cold-formed steel (CFS) sheets and hot-rolled steel (HRS) plates. The shear strength, load–deformation relationship, and failure mode of the specimens were obtained. The test results were compared with the results predicted by the North American Specification (AISI S 100–16), European Standard (EN1993-1–3), and finite element (FE) models. The influence of the fastener diameter and thickness of the CFS sheet and HRS plate on the specimens was discussed. In addition, a new method of calculating the bearing capacity of the connections with thicker plates was proposed. The results showed that bearing failure, shear failure, and combined bearing/shear failure were observed in the specimens. The nominal strengths predicted by AISI S 100 and EN 1993–1–3 for specimens are generally conservative. The numerical models can predict the failure modes and load–deformation relationships of the specimens with good agreement. In addition, the proposed method for the bearing capacity has better accuracy when the connections have thicker HRS plates.